Iridoid glycosides from Morinda tomentosa and their endoplasmic reticulum stress modulation activity - Giang, Vu Huong; Ban, Ninh Khac; Linh, Tran My; Lien, Le Quynh; Nhiem, Nguyen Xuan; Dung, Duong Thi; Tai, Bui Huu; Tuan Anh, Hoang Le; Yen, Pham Hai; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2015)
Three iridoids 1 - 3, asperulosidic acid, daphylloside, and asperuloside, were isolated from the methanol extract of the leaves of Morinda tomentosa. Their chemical structures were elucidated by 1D- and 2D-NMR spectra and in comparison with those reported in the literature. The effects of these compounds on the endoplasmic reticulum stress in XBP1-eGFP-transfected the 293 T cells were measured. Compound 3 significantly reduced the ER-stress both in DMSO-treated and thapsigargin-treated cells. Unlike this compound, compound 3 selectively reduced thapsigargin-induced ER-stress without any effect on the level of XBP1 splicing in DMSO-treated cells. These results suggested that compounds 2 and 3 can be suggested as new ER stress regulators.